Hubungan antara Self-Compassion dengan Resiliensi pada Remaja dari Keluarga yang Bercerai - Rusdiana, Alivia; Lestari, Mia Anita; Wijayani, Mira Rizki (Kasta: Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
This study aims to examine the relationship between self-compassion and resilience in adolescents from divorced families. Divorce is a major life event that can significantly impact adolescents' emotional and psychological well-being, often leading to challenges in adapting to changes in family structure. In this context, self-compassion—a personal trait involving kindness to oneself during suffering—may serve as an internal resource that enhances resilience. A total of 70 adolescents aged 10–19 years from divorced families participated in this study. They were selected using a purposive sampling technique. Data were collected using two main instruments: the Adolescent Resilience Scale (ARS), adapted from Oshio et al. (2003), and the Self-Compassion Scale (SCS), adapted from Neff (2003). The results of statistical analysis indicated that the null hypothesis was rejected. A Pearson correlation test revealed a strong and significant positive relationship between self-compassion and resilience (r = 0.733, p = 0.000). This finding suggests that adolescents who show greater self-compassion tend to possess higher levels of resilience in the face of parental divorce. Additional analyses showed that gender did not significantly affect either self-compassion or resilience levels, while age was found to be a significant factor influencing resilience. These results underline the importance of developing self-compassion in adolescents, particularly those undergoing family disruptions, as a protective factor to foster psychological adaptation and well-being.